ADAPTASI BERBAGAI VARIETAS TANAMAN KACANG HIJAU (Vigna radiata L.) TERHADAP PENGAPURAN DAN PEMBERIAN N, P DAN K DI LAHAN GAMBUT - Efi Rahmadani; Novianti Sunarlim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Research of variety adaptation, N, P, K fertilization and liming was conducted at research farm of Agriculture and Animal Science Faculty of Universitas Islam Negeri Sultan Syarif Kasim Riau from July to October 2011. The purpose of the study was to find the best variety of mungbean and the optimum dosage of N, P, K and lime planted in peat soils. The experiments were conducted in the pots. The first experiment was the variety adaptation using 15 varieties which were Bhakti, Gelatik, Kenari, Kutilang, Betet, Merak, Merpati, Camar, No. 129, Nuri, Parkit, Perkutut, Sampeong, Sriti dan Walet. The first factor of the second, third, fourth and fifth experiments were 5 varieties (Kutilang, Perkutut, Sampeong, Sriti dan Walet). The second factor was 3 levels of N fertilizers ((0, 100, 200 kg N/ha) for the second experiment, 3 levels of P fertilizers (0, 200, 400 kg P2O5/ha) for the third experiment, 3 levels of K fertilizers (0, 200, 400 kg K2O/ha) for the fourth experiment and 3 level of liming (0, 2,5, 5,0 t/ha dolomite/ha) for the fifth experiment. The experimental design used was Randomized Complete Block Design with 3 replications. Result of the experiments showed that Sampeong variety gave the highest number of pods/plant (14.3, 13.1, 15.1, 12.4 and 16.9 pods/plant for the first, second, third, fourth and fifth experiments respectively), but had the longest days to harvest (more than 70 days). The N fertilizer affected significantly number of pods/plant only until 100 kg N/ha. With this level number of pods increased from 6.8 with no N fertilizer to 9.3 per plant. The P fertilizer increased the number of pods/plant from 7.0 without P fertilizer to 10.1 with 200 kg P2O5/ha. Increasing P fertilizer above this level did not increase the number of pods/plant. Similarly, the optimum level for K fertilizer was 200 kg K20/ha which increased the number of pods from 7.2 with no K fertilizer to 9.2 per plant. The highest number of pods/plant was found from the higher level of lime. Applied 5 t/ha of dolomite increased pod/plant from 10.5 to 14.6